2019
DOI: 10.1126/sciadv.aaw6404
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for the age dependence of tau protein spread in the brain

Abstract: The incidence of Alzheimer’s disease (AD), which is characterized by progressive cognitive decline that correlates with the spread of tau protein aggregation in the cortical mantle, is strongly age-related. It could be that age predisposes the brain for tau misfolding and supports the propagation of tau pathology. We tested this hypothesis using an experimental setup that allowed for exploration of age-related factors of tau spread and regional vulnerability. We virally expressed human tau locally in entorhina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
106
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(128 citation statements)
references
References 39 publications
19
106
1
2
Order By: Relevance
“…In our study, using the Drosophila in-vivo model, we demonstrate that human tau propagates trans-cellularly from the site of targeted expression to the additional regions of the adult fly brain by the factor of age. Hence, our finding is in line with the previous reports which also proclaim the migration of tau pathology in other model systems [13,14].…”
Section: Introductionsupporting
confidence: 94%
“…In our study, using the Drosophila in-vivo model, we demonstrate that human tau propagates trans-cellularly from the site of targeted expression to the additional regions of the adult fly brain by the factor of age. Hence, our finding is in line with the previous reports which also proclaim the migration of tau pathology in other model systems [13,14].…”
Section: Introductionsupporting
confidence: 94%
“…Several in vitro [ 95 ] and in vivo studies [ 96 , 97 , 98 , 99 ] have revealed that tau is transmitted from one cell to another following a stereotypical pattern, thus supporting the tau prion propagation hypothesis in AD and other tauopathies [ 100 ]. Although these observations provide solid evidence of this phenomenon, the mechanisms of tau release, internalization, and processing are still being studied.…”
Section: Tau Proteinmentioning
confidence: 91%
“…Tau proteins (or Tau aggregates) migrate along nerve fibers and thus contribute to the spread of the disease throughout the brain [74]. If proteins spread more quickly in the aging brain, this might explain why most people with Alzheimer's disease are older [75].…”
Section: Tau Inhibitionmentioning
confidence: 99%